Glued timber concrete composite walls using ultra-high-performance concrete - Thomas Oberndorfer; Frank Hunger; Oliver Fischer (Acta Polytechnica CTU Proceedings, 2022)
This paper gives a short introduction of the development of cross laminated timber (CLT) concrete composite walls with a glued connection. In the composite walls, prefabricated ultra-high-performance concrete (UHPC) lamellas replace timber lamellas at the core layer of the CLT elements. To check the feasibility of gluing timber to UHPC small-scale shear, delamination and bonding tests were performed and showed promising results. The load bearing behaviour was analysed with centrically and eccentrically loaded tests on wall segments. Analytic modelling of the wall experiments using an effective bending stiffness, based on shear analogy method, showed a good correlation to the experimental results.